HNO Is Produced by the Reaction of NO with Thiols - Suarez, Sebastian (2017)
Azanone (nitroxyl, HNO) is a highly reactive compound whose biological role is still a matter of debate. One possible route for its formation is NO reduction by biological reductants. These reactions have been historically discarded due to the negative redox potential for the NO,H+/HNO couple. However, the NO to HNO conversion mediated by vitamins C, E, and aromatic alcohols has been recently shown to be feasible from a chemical standpoint. Based on these precedents, we decided to study the reaction of NO with thiols as potential sources of HNO. Using two complementary approaches, trapping by a Mn porphyrin and an HNO electrochemical sensor, we found that under anaerobic conditions aliphatic and aromatic thiols (as well as selenols) are able to convert NO to HNO, albeit at different rates. Further mechanistic analysis using ab initio methods shows that the reaction between NO and the thiol produces a free radical adduct RSNOH•, which reacts with a second NO molecule to produce HNO and a nitrosothiol. The nitrosothiol intermediate reacts further with RSH to produce a second molecule of HNO and RSSR, as previously reported.